DETERMINATION OF THE RUTIN, QUERCETIN AND KAEMPFEROL CONTENTS IN A GHANAIAN POLYHERBAL FORMULATION (EAF-2011) AND ITS RAW MATERIALS USING A SIMULTANEOUS RP-HPLC METHOD (International Journal of Pharmaceutical Sciences and Drug Research, 2015)
Quantitative chemical fingerprinting of herbal medicines provides an avenue for addressing the challenge with their quality. In this report, chemical markers that could be labelled as active markers in the polyherbal product and its component raw materials were assayed using a simultaneous RP-HPLC method. These markers were rutin (RU), quercetin (QE) and kaempferol (KA) which are well known for their antimicrobial activities. The quantitative assay of the markers using a validated HPLC method showed the herbal product (EAF-2011) contained 8.6810% (w/w) of rutin, 0.2670% (w/w) of quercetin and 0.0610% (w/w) of kaempferol. At least two (2) of these flavonoids were detected in each of the component raw plant materials: Psidium guajava [(RU-8.5860% (w/w); QE-0.5430% (w/w); KA - 0.1003% (w/w)], Alchornea cordifolia [RU-2.5540% (w/w); QE-0.0536% (w/w)], Zanthoxylum zanthoxyloides [RU-5.8060 % (w/w); KA-0.0174% (w/w)], Tridax procumbens [RU-2.4390% (w/w); QE-0.1040% (w/w); KA-0.0510% (w/w)] and Eugenia caryophyllata [QE-0.4080% (w/w); KA-0.0771% (w/w)]. The results obtained indicate that the HPLC method, selected chemical markers and chromatograms produced are ideal for the quality control of the product and its component raw materials.